You can try them out and see which one works.
a: f(2) = f(1) +6 = 5+6 = 11 . . . . . . not this one
b: f(1) = f(2) -6 = -1-6 = -7 . . . . . . not this one (5 ≠ -7)
c: f(2) = f(1) - 6 = 5 - 6 = -1 . . . . . this gives the right f(2)
d: f(2 = -6(f(1) = -6(5) = -30 . . . . not this one
_____
The appropriate choice is ...
... f(n +1) = f(n) - 6
— — — — —
You can also recognize that the next term is 6 less than the current one, so f(n+1) = f(n) - 6, which corresponds to the 3rd selection.
Answer:
Step-by-step explanation:
The factor pairs of 6 are 1×6 and 2×3
So the parallelogram (height by length) could be:
1 by 6
2 by 3
3 by 2
6 by 1
That is correct since the line in T is not straight it would eventually hit the third quadrant
<span />
Answer:
352
Step-by-step explanation:
:)
:)
:)
Answer:
b
Step-by-step explanation: